1991
DOI: 10.1002/bit.260370205
|View full text |Cite
|
Sign up to set email alerts
|

Crossflow microfiltration of animal cells

Abstract: Laminar shear is the primary mechanism of cell damage, limiting flow rate (and hence flux) in crossflow microfiltration of animal cells. Sensitivity to hydrodynamic and interfacial stress is reduced by the addition of 0.1% Pluronic polyol. A critical average wall shear rate of 3000 s(-1) (above which damage occurs) is found for several cell types, including mammalian and insect cells. Hydrodynamic stress also limits the maximum tip speed in a rotary lobe pump to less than 350 cm/s. Turbulent flow in the recirc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 24 publications
3
60
1
Order By: Relevance
“…The surfactant lowers the interfacial tension between the membrane surface and the attached cells and hence enhances their recovery. The possibility that microfiltration may damage cells due to stress induced by the laminar shear field or by deformation of the cell in filter pores under the transmembrane pressure was also examined in our work (30). The extent of shear damage depends on the intensity, duration, and type of shear force and also on the cell type and growth stage (31).…”
Section: Discussionmentioning
confidence: 87%
“…The surfactant lowers the interfacial tension between the membrane surface and the attached cells and hence enhances their recovery. The possibility that microfiltration may damage cells due to stress induced by the laminar shear field or by deformation of the cell in filter pores under the transmembrane pressure was also examined in our work (30). The extent of shear damage depends on the intensity, duration, and type of shear force and also on the cell type and growth stage (31).…”
Section: Discussionmentioning
confidence: 87%
“…Maiorella et al (1991) reported that cells were damaged at wall shear rates over 6000 s −1 , while Zhang et al (1993) observed a drop in culture viability at a shear rate of 1300 s −1 during perfusion using a hollow-fiber cartridge. Higher shear rates require higher inlet pressures and thus also increase the transmembrane pressure difference at the filter inlet.…”
Section: Cross-flow Filtersmentioning
confidence: 99%
“…The improvement for more complex scenarios can be significant enough to invest in better models and advanced control configuration. 3 where ith order time derivatives will be considered with i = {1, 2, . .…”
Section: Discussionmentioning
confidence: 99%
“…Consider now a case where we want to arrive at final point [5,3.97] (square in Fig. 4) starting from the same initial point.…”
Section: Case Study 1: Separation Of Lactose From Proteinsmentioning
confidence: 99%
See 1 more Smart Citation